2020
DOI: 10.1083/jcb.201912061
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of clathrin heavy chain contributes to the switch from coated pits to plaques

Abstract: Clathrin function directly derives from its coat structure, and while endocytosis is mediated by clathrin-coated pits, large plaques contribute to cell adhesion. Here, we show that the alternative splicing of a single exon of the clathrin heavy chain gene (CLTC exon 31) helps determine the clathrin coat organization. Direct genetic control was demonstrated by forced CLTC exon 31 skipping in muscle cells that reverses the plasma membrane content from clathrin plaques to pits and by promoting exon inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 60 publications
4
42
0
Order By: Relevance
“…To estimate the curvature of the CCSs, the mean CCS ROI was divided by the average grey value of the PM (as determined by the mean grey value of 4 PM ROIs in each corner of each image). From these two values, the morphology of the CCS could be determined by using thresholds and divided into categories, as described by Moulay et al ., ( 21 ). We used an area threshold of 8500 mm 2 (which is derived from a diameter of 105 nm) to determine if the CCS was small or large, and a curvature value of 1.25 (determined by measuring the mean grey value of the large CCSs observed in TPC disruption conditions) to determine if the CCS was round or flat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate the curvature of the CCSs, the mean CCS ROI was divided by the average grey value of the PM (as determined by the mean grey value of 4 PM ROIs in each corner of each image). From these two values, the morphology of the CCS could be determined by using thresholds and divided into categories, as described by Moulay et al ., ( 21 ). We used an area threshold of 8500 mm 2 (which is derived from a diameter of 105 nm) to determine if the CCS was small or large, and a curvature value of 1.25 (determined by measuring the mean grey value of the large CCSs observed in TPC disruption conditions) to determine if the CCS was round or flat.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the effect of TPC disruption, we determined the shape of the clathrin structures by measuring the area and average intensity (a proxy for CCV curvature (Fig. S4A) ( 21 )) of each clathrin structure visualized and classified these shapes into 4 categories; ‘small and round’ (the fully invaginated CCVs), ‘small and flat’ (where curvature generation had failed), ‘large and round’, and ‘large and flat’ (clathrin plaques) (Fig. 3C).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the curvature of the CCSs, the mean CCS ROI was divided by the average gray value of the PM (as determined by the mean gray value of 4 PM ROIs in each corner of each image). From these two values, the morphology of the CCS could be determined by using thresholds to divide the CCSs into categories as described by Moulay et al (24). We used an area threshold of 8,500 mm 2 (which is derived from a diameter of 105 nm) to determine if the CCS was small or large and a curvature value of 1.25 (determined by measuring the mean gray value of the large CCSs observed in TPC disruption conditions) to determine if the CCS was round or flat.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of SMAP-1, we found that the remaining CHC-1-labeled structure no longer colocalized with APG-1 ( Figure 5C-C′ ). In addition to biosynthetic sorting, the clathrin coat is known to mediate the formation of endocytic clathrin-coated vesicles ( Chen and Schmid, 2020 ; Moulay et al, 2020 ). Also, clathrin has been reported to function as a component of the retrograde transport machinery on the surface of the endosome ( Saint-Pol et al, 2004 ; Shi et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%